Identification of vacuolar autophagic aggregates in the skeletal muscles of inbred C57BL/6NCrl mice. (June 2023) - De Biase, Davide; Pagano, Teresa Bruna; Malanga, Donatella; Russo, Valeria; Piegari, Giuseppe; d'Aquino, Ilaria; Iovane, Valentina; Scarfò, Marzia; Papparella, Serenella; Wojcik, Slawomir; Paciello, Orlando
A comprehensive pathological analysis of inbred strains is essential to define strain-specific spontaneous lesions and to understand whether a specific phenotype results from experimental intervention or reflects a naturally occurring disease. This study aimed to report and describe a novel condition affecting the skeletal muscles of an inbred C57BL/6NCrl mouse colony characterised by large sarcoplasmic vacuoles in the muscle fibres of male mice in the subsarcolemmal spaces and the intermyofibrillary network. There was no muscle weakness, loss of ambulation or cardiac/respiratory involvement. Post-mortem evaluation and histological analysis excluded the presence of pathological accumulations or lesions in other tissues and organs. Changes were seen in fibre size, with many hypotrophic and some slightly hypertrophic fibres. Histological, immunohistochemical and molecular analyses of the vacuolar content revealed dysregulation of the autophagy machinery while ruling out a morphologically similar condition marked by the accumulation of tubular aggregates.